Experience of violence among the health care workers tertiary care hospitals of Kathmandu Metropolitan city - A cross sectional study. - Pokhrel,Diksha (2021)
ABSTRACT: Introduction: Violence, the overall leading cause of death in worldwide population of 15-44 years, is defined by WHO as "the intentional use of physical force or power, threatened or actual, against oneself, another person, against a group or community that either results in or has a high likelihood of resulting injury or death, psychological harm, mal-development or deprivation." Healthcare workers are 16 times more prone to experiencing violence than any other profession. This study intends to look at two forms of violence that occurs to the healthcare workers: Professional (Workplace) and Domestic (Home-based) violence. Workplace violence refers to any physical assault, threating verbal abuse or any intimidating behavior that occurs in a workplace while domestic violence is a learned behavior to gain power or control over a family member. Methodology: A cross-sectional analytical study was conducted in four tertiary care hospitals of Kathmandu Metropolitan City namely: Kathmandu Medical College, Bir Hospital, Institute of Medicine and Nepal Medical College. The study participants were NMC registered Doctors and NNC registered Nurses. This study explored the prevalence, risk factors, perpetrators, impacts and co-existence of different forms of violence. Results: The prevalence of workplace violence (49.8%) was higher than domestic violence (10.1%). verbal violence (88%) was the most common form of violence in workplace while psychological violence (47.1%) was the common from in domestic violence. The perpetrators in Workplace violence were patient's relatives (78.4%) and Supervisors (39.6%) whereas in Domestic violence the perpetrators were parents/ guardians / relatives or present/ former partner. Males, above 30 years of age, working in the Emergency department were found to be at higher risk of experiencing workplace violence. Participants reported feeling disappointed, angry, humiliated, irritated and insecure due to violence leading to less care for the patient (7.7%) and thought of quitting the profession (8.2%). Only in 8.2% of the reported incidents, some action was taken which was mostly only a verbal warning. While males had higher odds of experiencing physical type of domestic violence, , females experienced psychological and sexual violence more. More than 1/3rd participants experiencing domestic violence felt betrayed and although 67.6% of the participants accepted begin left with some kind of psychological impact due to violence, only 2.7% sought help. 86.48% of the participants who experienced any form of domestic violence admitted to have experiences workplace violence highlighting the co-existence of violence and the odds of experiencing workplace violence was 7.6 times higher in those experiencing domestic violence. Conclusion: This high prevalence rate of violence in our study concludes that violence in healthcare workers is under-explored and under-reported problem that is very crucial to be explored and taken preventive measures. Healthy workplace and healthy living environment is the right to every citizen and should not be overlooked in doctors and nurses solely because they are considered privileged groups of individuals. Violence impacts both professional and personal life of an individual so this problem should be taken with extreme sincerity. Key words: Violence, workplace violence, domestic violence, perpetrators, Impacts, Physical, Verbal, Emotional, Psychological, Co-existence of violence.